Galectin-3 inhibition ameliorates hepatic steatosis in a multilineage 3D spheroid model - Francesca Sedda; Andrea Caddeo; Kavitha Sasidharan; Giovanni Perra; Rajesh Pal; Nicola Lai; Marta Anna Kowalik; Andrea Perra (PLoS ONE, 2025)
Background Metabolic dysfunction-associated steatotic liver disease (MASLD) is the leading cause of chronic liver disease, and liver-related morbidity and mortality worldwide. MASLD is a multifactorial condition, which still needs to be completely understood. Galectin 3 (Gal-3) is up-regulated in several liver disorders suggesting its implication in the mechanisms underlying liver damage. Methods A human multilineage 3D model was utilized to investigate the role of Gal-3 in MASLD development. Human hepatoma cell line (HepG2) and human stellate cell line (LX-2) were co-cultured in a physiological ratio of 24:1 and treated with a mixture of palmitic and oleic acid (PAOA, ratio 1:2) to induce hepatocyte steatosis and facilitate the development of fibrosis. While the effect of LGALS3 silencing on neutral fat content was assessed by Oil-Red-O (ORO) staining, type I collagen production was analysed by immunofluorescent staining for collagen type I alpha 1 (COL1A1). Results Gal-3 depletion caused a reduction of neutral lipid content and COL1A1 accumulation in 3D spheroids. While LGALS3 silencing did not significantly alter the respiratory state, analysis of genes involved in lipid metabolism demonstrated significant changes in genes involved in β-oxidation and triglyceride synthesis. Conclusion These results suggest a role of Gal-3 in the regulation of fatty acid and collagen accumulation, thereby indicating that approaches aimed at inhibiting Gal-3 may represent a promising therapeutic strategy in MASLD.